Alkaloid-Rich Crude Extracts, Fractions and Piperamide Alkaloids of Piper guineense Possess Promising Antibacterial Effects - Eunice Ego Mgbeahuruike; Pia Fyhrquist; Heikki Vuorela; Riitta Julkunen-Tiitto; Yvonne Holm (MDPI AG, 2018)
Piper guineense is a food and medicinal plant commonly used to treat infectious diseases in West-African traditional medicine. In a bid to identify new antibacterial compounds due to bacterial resistance to antibiotics, twelve extracts of P. guineense fruits and leaves, obtained by sequential extraction, as well as the piperine and piperlongumine commercial compounds were evaluated for antibacterial activity against human pathogenic bacteria. HPLC-DAD and UHPLC/Q-TOF MS analysis were conducted to characterize and identify the compounds present in the extracts with promising antibacterial activity. The extracts, with the exception of the hot water decoctions and macerations, contained piperamide alkaloids as their main constituents. Piperine, dihydropiperine, piperylin, dihydropiperylin or piperlonguminine, dihydropiperlonguminine, wisanine, dihydrowisanine and derivatives of piperine and piperidine were identified in a hexane extract of the leaf. In addition, some new piperamide alkaloids were identified, such as a piperine and a piperidine alkaloid derivative and two unknown piperamide alkaloids. To the best of our knowledge, there are no piperamides reported in the literature with similar UVλ absorption maxima and masses. A piperamide alkaloid-rich hexane leaf extract recorded the lowest MIC of 19 µg/mL against Sarcina sp. and gave promising growth inhibitory effects against S. aureus and E. aerogenes as well, inhibiting the growth of both bacteria with a MIC of 78 µg/mL. Moreover, this is the first report of the antibacterial activity of P. guineense extracts against Sarcina sp. and E. aerogenes. Marked growth inhibition was also obtained for chloroform extracts of the leaves and fruits against P. aeruginosa with a MIC value of 78 µg/mL. Piperine and piperlongumine were active against E. aerogenes, S. aureus, E. coli, S. enterica, P. mirabilis and B. cereus with MIC values ranging from 39⁻1250 µg/mL. Notably, the water extracts, which were almost devoid of piperamide alkaloids, were not active against the bacterial strains. Our results demonstrate that P. guineense contains antibacterial alkaloids that could be relevant for the discovery of new natural antibiotics.